"I've never been that traditional domestic Turkish woman": Self, culture, and the dissociative mind. Issue 1 (2nd January 2020) - Eğit, Esin
Abstract: There is an increasing overlap between contemporary interpersonal/relational theories and psychological anthropology, especially related in their conceptual formulations of, respectively, the self and culture as dynamic, multiplicious, and discontinuous process. The author argues that these corresponding formulations behoove us consider self and culture are interwoven processes that continuously inform and shape each other, and are shaped by dissociative mental processes. Drawing from a series of ethnographic interviews and participant observation conducted among a cohort of Turkish women, the author argues during the process of enculturation, people learn pertinent, yet devalued, aspects of their culture, and incorporate them into their self-consciousness disjointly. These disjointed aspects of the self can become activated, however, during experiences of cultural discontinuity; the result is often disorganization and inner-conflict regarding identity.